PENGARUH PENDAPATAN ASLI DAERAH TERHADAP BELANJA DAERAH DI KOTA MANADO PROVINSI SULAWESI UTARA (The Effect of Regional Original Revenue to Regional Expenditures in Manado City North Sulawesi) - Imanuel M. H. Sumakul; Theodora M. Katiandagho; Melissa L. G. Tarore (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2020)
The objective of this study is to analyze the Effect of Regional Original Revenue on Regional Expenditures in Manado City North Sulawesi Province. The variables to be analyzed are regional original revenue (PAD) and Regional Expenditures from 2000-2017. This research was conducted in June to December 2019, from preparation to report preparation.Â Secondary data used obtained from relevant agencies, the statistical center of Manado City.Â Secondary data collected from Regional Original Revenue (PAD) and Regional Expenditures with time series data for 18 years.Â The method of data analysis is done using simple Regression Analysis. The research results showed that the Regional Original Revenue has a positive and significant effect on Regional Expenditure in the Manado City, North Sulawesi Province.Keywords: Effect of local original revenue, local expenditure